Modern Concept Of Entrepreneurship Islamic Perspective And Its Practice In Indonesia - Achmad Zulfikar Siregar; Epan Apanda; Soleman Jahrul Harianja; Fauzan Hilal Zuhri (SEAN Institute, 2022)
Islam is the most perfect religion in all respects. One of its perfections is to oblige its people to be able to live independently by working or doing business in the right way. Islam not only teaches to worship, but Islam also teaches its people to be independent and work hard, one of which is entrepreneurship. Entrepreneurship is a science that studies the values, abilities, and behavior of a person in facing life's challenges. Entrepreneurial elements include motivation, vision, communication, optimism, encouragement and the ability to take advantage of opportunities. Islamic entrepreneurship is an aspect of life that is grouped into muamalah issues. Problems that are closely related to horizontal relationships, namely the relationship between humans that will be accounted for later in the hereafter. Islamic entrepreneurship is a worship that will get a reward if it is implemented.